1999
DOI: 10.1016/s0022-5347(01)61988-8
|View full text |Cite
|
Sign up to set email alerts
|

A Non-Nitrergic Smooth Muscle Relaxant Factor Released From Rat Urinary Bladder by Muscarinic Receptor Stimulation

Abstract: A previously unrecognized non-adrenergic, non-nitrergic, non-prostanoid inhibitory mediator is released from the rat urinary bladder by muscarinic receptor stimulation. The physiological importance of such a factor remains to be established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 18 publications
1
35
1
Order By: Relevance
“…It was resistant to inhibition of the L-arginine/nitric oxide and COX pathways and remained unaffected by propranolol. The effect was interpreted as being caused by an unidentified relaxant factor released from bladder tissue (Fovaeus et al, 1999). The presence of a relaxant factor, released from the rat bladder by acetylcholine, was confirmed by Inci et al (2003), who also showed that bladder inflammation did not alter the synthesis and/or release of this bladder-derived relaxant factor.…”
Section: Peripheral Targetsmentioning
confidence: 85%
See 2 more Smart Citations
“…It was resistant to inhibition of the L-arginine/nitric oxide and COX pathways and remained unaffected by propranolol. The effect was interpreted as being caused by an unidentified relaxant factor released from bladder tissue (Fovaeus et al, 1999). The presence of a relaxant factor, released from the rat bladder by acetylcholine, was confirmed by Inci et al (2003), who also showed that bladder inflammation did not alter the synthesis and/or release of this bladder-derived relaxant factor.…”
Section: Peripheral Targetsmentioning
confidence: 85%
“…It has been suggested that factors released from the urothelium should be able to modify the bladder response to distension (Andersson, 2002b), similar to what is found in the endothelium and vascular smooth muscle (Burnstock, 1999). Unidentified smooth muscle-relaxing factors, released from the bladder wall and/or the urothelium and causing bladder relaxation, have been described (Levin et al, 1995;Fovaeus et al, 1998Fovaeus et al, , 1999Hawthorn et al, 2000;Templeman et al, 2002). Fovaeus et al (1999), using a coaxial bioassay system with endothelium-free, noradrenaline-contracted rat aortic preparations mounted within urothelium-intact urinary bladder, showed that carbachol caused a concentration-dependent relaxation of the vessel preparation.…”
Section: Peripheral Targetsmentioning
confidence: 99%
See 1 more Smart Citation
“…There seem to be other, thus far unidentified, factors in the urothelium that could influence bladder function (103,128,271). Thus muscarinic receptor stimulation was found to release a previously unrecognized nonadrenergic, nonprostanoid inhibitory factor from the rat urinary bladder (103).…”
Section: Bladder Overactivitymentioning
confidence: 99%
“…Thus muscarinic receptor stimulation was found to release a previously unrecognized nonadrenergic, nonprostanoid inhibitory factor from the rat urinary bladder (103). It could not be determined whether the factor was released from the urothelium or the detrusor or from both tissues (103). However, other investigators reported that a diffusible, nonidentified inhibitory factor appearing to be neither NO, a cyclooxygenase product, a catecholamine, adenosine, GABA, nor any substance sensitive to apamin, was released from the urothelium (128).…”
Section: Bladder Overactivitymentioning
confidence: 99%